2019
DOI: 10.5897/jpp2019.0547
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory activities of polysaccharides isolated from plants used as antimalarial in Mali

Abstract: Medicinal plants used against malaria in Mali have previously been tested for their antiplasmodial activities using their organic solvent and water extracts. As the healers mainly use the water extracts for their treatments of malaria-patients, our aim was to study the water-soluble components from Malian plants used for treatment of malaria. Argemone mexicana (aerial parts), Sarcocephalus latifolius (root bark), Vitex doniana (leaves), and Malarial-5 ® (an improved traditional medicine (ITM) in tea) were the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Several studies have reported the analgesic activity [148, 149] and anti-inflammatory property [150,151] of S. latifolius. Polysaccharides from aqueous extracts of the trunk bark of S. latifolius showed immunostimulant activity [152]. S. latifolius also possessed antiradical and antioxidant properties in vivo and in vitro [144,151,153].…”
Section: Mitragyna Inermis (Willd) O Kuntze (Rubiaceae)mentioning
confidence: 97%
“…Several studies have reported the analgesic activity [148, 149] and anti-inflammatory property [150,151] of S. latifolius. Polysaccharides from aqueous extracts of the trunk bark of S. latifolius showed immunostimulant activity [152]. S. latifolius also possessed antiradical and antioxidant properties in vivo and in vitro [144,151,153].…”
Section: Mitragyna Inermis (Willd) O Kuntze (Rubiaceae)mentioning
confidence: 97%
“…There is therefore a need to find new drugs that are both effective and accessible. Apart from the fact that the two current first-line antimalarial compounds, come from traditional medicine: Quinine, isolated from Cinchona officinalis L. [9] from traditional Peruvian medicine and artemisinin, isolated from the leaves Artemisia annua L. [10] , formerly used in traditional Chinese medicine; previous work reports that traditional African medicine has provided improved traditional medicines such as Malarial 5® [11] , Malaria® [12] currently use in DR Congo. In addition, traditional medicine offers strong compliance as long as more than 80% of the world population uses it as a first line [13] .…”
Section: Introductionmentioning
confidence: 99%